Match activity demands of elite Spanish female basketball players by playing position - Delextrat, A.; Badiella, A.; Saavedra, V.; Matthew, D.; Schelling, X.; Torres-Ronda, L. (International Journal of Performance Analysis in Sport, 2015)
The primary aim of this study was to identify the effects of playing position on match activities of female basketball players. A secondary aim was to compare these match activities between quarters of play. Forty-two elite females players (25.9±4.3y, 183.4±9.0 cm) were studied during competitive matches. The frequency, duration and percentage of live time (%LT) were calculated. Differences between playing positions (PG, SG, SF, PF and C) and quarters were analyzed using repeated measures ANOVA. Results showed significantly more movements in PG than other positions (25.6±2.8 per min vs. 21.2±2.2 to 23.6±2.6 per min, P = 0.022), and more sprints in PG than PF and C (0.4±0.2 per min vs. 0.1±0.1 and 0.1±0.1, respectively for PG, PF and C, P = 0.040). Furthermore, PF and C performed more jumps and static exertion than other positions (jump frequencies and %LT static exertion of 1.2±0.2 per min and 4.8±2.1% for PF, 1.5±0.3 per min and 7.1±2.2% for C vs. 0.7±0.3 to 1.0±0.2 per min and 1.7±0.6 to 3.4±1.2 % in other positions, P = 0.002 to 0.028). A decrease in %LT for high-intensity movements was observed in the 4th compared to 1st and 3rd quarters (P = 0.048). These results highlight that physical conditioning by playing position might be worth considering by coaches, although longitudinal training studies are necessary to confirm this observation.